Biosurfactants and its Applications in Aquaculture - Nadella, Ranjit Kumar; Muthulakshmi, T.; Minimol, V. A.; Murugadas, V.; Basha, K. A.; Joseph, Toms C.; Prasad, M. M. (Fishery Technology, 2020)
Aquatic environments harbour a wide diversity of microorganisms that produce several novel compounds. Biosurfactant is a compound synthesized by microorganisms which have distinct physiological and metabolic pathways. Structurally they are amphiphilic molecules with hydrophilic moiety (tail) and hydrophobic moiety (head) that accumulates between two fluid phases and reduces surface tension. The property of a particular biosurfactant molecule is dependent on the location as well as the size of the functional groups. These biosurfactants can form strong emulsions at wide ranges of pH and temperature. The physico-chemical and biological properties are unique which makes the biosurfactant widely applicable in different fields, including aquaculture. Most common applications include inhibition of quorum sensing mechanism of the bacterial communication and inhibiting the growth of pathogenic bacteria. In case of fish feed processing industries, the emulsions formed by the biosurfactant can be incorporated into diet. The micelle forming property of the biosurfactant can be exploited for developing targeted drug delivery techniques. The methodologies and techniques for screening potential microorganisms which produce biosurfactant from aquatic environment and its application in aquaculture sector assume great importance. This communication provides a detailed review on the developments in these areas.